A generalization of a theorem of Faith and Menal and applications - Kentaro Tsuda (International Journal of Mathematics and Mathematical Sciences)
In 1995, Faith and Menal have established the V -ring theorem which gives a characterization of a V-ring. In this paper, we generalize this theorem to V-modules and consider some applications for Noetherian self-cogenerators.